Mycotoxins and the intestine - Broom, Leon (Anim Nutr, 2015)
Fungal biochemical pathways can yield various compounds that are not considered to be necessary for their growth and are thus referred to as secondary metabolites. These compounds have been found to have wide ranging biological effects and include potent poisons (mycotoxins). Mycotoxins invariably contaminate crops and (thus) animal feeds. The intestine is the key link between ingested mycotoxins and their detrimental effects on the animal. Effects on the intestine, or intestinal environment, and immune system have been reported with various mycotoxins. These effects are almost certainly occurring across species. Most, if not all, of the reported effects of mycotoxins are negative in terms of intestinal health, for example, decreased intestinal cell viability, reductions in short chain fatty acid (SCFA) concentrations and elimination of beneficial bacteria, increased expression of genes involved in promoting inflammation and counteracting oxidative stress. This challenge to intestinal health will predispose the animal to intestinal (and systemic) infections and impair efficient digestion and absorption of nutrients, with the associated effect on animal productivity.